Cell cycle arrest of a Caulobacter crescentus secA mutant. - Kang, P J (1994)
Cell differentiation is an inherent component of the Caulobacter crescentus cell cycle. The transition of a swarmer cell, with a single polar flagellum, into a sessile stalked cell includes several morphogenetic events. These include the release of the flagellum and pili, the proteolysis of chemotaxis proteins, the biogenesis of the polar stalk, and the initiation of DNA replication. We have isolated a group of temperature-sensitive mutants that are unable to complete this process at the restrictive temperature. We show here that one of these strains has a mutation in a homolog of the Escherichia coli secA gene, whose product is involved in protein translocation at the cell membrane. This C. crescentus secA mutant has allowed the identification of morphogenetic events in the swarmer-to-stalked cell transition that require SecA-dependent protein translocation. Upon shift to the nonpermissive temperature, the mutant secA swarmer cell is able to release the polar flagellum, degrade chemoreceptors, and initiate DNA replication, but it is unable to form a stalk, complete DNA replication, or carry out cell division. At the nonpermissive temperature, the cell cycle blocks prior to the de novo synthesis of flagella and chemotaxis proteins that normally occurs in the predivisional cell. Although interactions between the chromosome and the cytoplasmic membrane are believed to be a functional component of the temporal regulation of DNA replication, the ability of this secA mutant to initiate replication at the nonpermissive temperature suggests that SecA-dependent events are not involved in this process. However, both cell division and stalk formation, which is analogous to a polar division event, require SecA function.